Crickets (Acheta domesticus) as Wheat Bread Ingredient: Influence on Bread Quality and Safety Characteristics - Bartkiene, Elena (2023)
The aim of this study was to assess respondents’ opinions on the choice of edible insects as a food, and to evaluate the influence of cricket flour (ECF) (10, 20, 30%) on the quality of wheat bread (WB). Whereas ECF is an additional source of acrylamide precursors, in order to reduce acrylamide formation in WB, fermentation of ECF with Lactiplantibacillus plantarum-No.122 was applied. It was established that 70.7% of the respondents had never eaten insects and more than 30% would not choose them. However, ECF was suitable substrate for fermentation (lactobacilli count 8.24 log10CFU/g, pH-4.26). In addition, fermentation reduced the total biogenic amines content in ECF (by 13.1%). The highest specific volume showed WB, prepared with fermented ECF (10, 20, 30%). All the tested WB showed similar overall acceptability (on average, 7.9 points). However, the highest intensity of emotion “happy” was induced by the WB, prepared with fermented ECF. Most of the WB with non-treated and fermented ECF showed higher acrylamide concentration (except WB with 10% of fermented ECF), in comparison with the control. Finally, fermentation is recommended for ECF inclusion in the main WB formula because fermentation improves not only quality but also reduces acrylamide concentration in WB.